Microstructural controls on the physical and mechanical properties of edifice‐forming andesites at Volcán de Colima, Mexico. Issue 4 (23rd April 2014) - Heap, M. J.; Lavallée, Y.; Petrakova, L.; Baud, P.; Reuschlé, T.; Varley, N. R.; Dingwell, D. B.
Abstract: The reliable assessment of volcanic unrest must rest on an understanding of the rocks that form the edifice. It is their microstructure that dictates their physical properties and mechanical behavior and thus the response of the edifice to stress perturbations during unrest. We evaluate the interplay between microstructure and rock properties for a suite of edifice‐forming rocks from Volcán de Colima (Mexico). Microstructural analyses expose (1) a pervasive, isotropic microcrack network, (2) a high, subspherical vesicle density, and (3) a wide vesicle size distribution. This complex microstructure severely impacts their physical and mechanical properties. In detail, porosities are high and range from 8 to 29%. As a consequence, elastic wave velocities, Youngs moduli, and uniaxial compressive strengths are low, and permeabilities are high. All of the rock properties demonstrate a wide range. For example, strength decreases by a factor of 8 and permeability increases by 4 orders of magnitude over the porosity range. Below a porosity of 11–14%, the permeability‐porosity trend follows a power law with a much higher exponent. Microstructurally, this represents a critical vesicle content that efficiently connects the microcrack population and permits a much more direct path through the sample, rather than restricting flow to long and tortuous microcracks. Values of tortuosity inferred from the Kozeny‐Carman permeability model support this hypothesis. However, we find that the complex microstructure precludes a complete description of their mechanical behavior through micromechanical modeling. We urge that the findings of this study be considered in volcanic hazard assessments at andesitic stratovolcanoes. Key Points: Andesites from Volcán de Colima are microstructurally complex Their microstructural complexity influences their properties Micromechanical modeling is therefore a challenge